Manual acupuncture for postoperative pain and recovery after abdominal surgeries: a systematic review - Staff, Sophie; Yang, Cui; Greten, Henry Johannes; Braun, Volker; Reißfelder, Christoph; Herrle, Florian; Ghanad, Erfan (Journal of integrative and complementary medicine, 2025)
Introduction: Acupuncture’s role in surgical and postoperative contexts is gaining traction. However, the evidence remains patchy and is often of low-grade quality, particularly in the context of postintestinal surgery. - Purpose: To assess acupuncture’s efficacy in pain relief and functional recovery after abdominal surgery. - Methods: We searched PubMed, Cochrane, Web of Science, and Google Scholar for randomized trials using manual acupuncture as the main intervention. Outcomes included postoperative pain, analgesic use, nausea, gastrointestinal (GI) regeneration, and length of hospital stay. For risk of bias assessment Cochrane risk of bias tool 2 was employed. Registered with PROSPERO: CRD42022311718. - Results: Of 700 records till May 2023, 8 trials (551 patients; 16-200/trial) were included. Due to factors such as varying experimental settings and unpublished protocols, there was high risk of bias and heterogeneity, making meta-analysis unfeasible. Safety data were documented sufficiently by two trials. However, acupuncture showed marked benefits in pain relief, less analgesic use, fewer nausea cases, and improved GI recovery. One study reported reduced hospitalization time. - Conclusion: Due to the varied methodologies and potential biases in existing studies, the definitive effectiveness of acupuncture remains unclear. To confirm the potential benefits of acupuncture as suggested by the reviewed studies, it’s imperative to have more standardized study protocols, well-defined interventions and controls, and objective measures of efficacy.
Gesehen am 31.03.2025